Interaction of insecticide and disinfectants used in a poultry house with the nematode entomopathogenic Steinernema arenarium (Research, Society and Development, 2020)
This study evaluated the effect of cypermethrin insecticide and disinfectants, both used in the management of poultry houses, on nematode Steinernema arenarium, as well as their effect on the bacterium symbiont of nematode. The IOBC/WPRS methodology proposed by Vainio (1992) was used to study the effect on the nematode. The solution of the product was mixed with 1ml of the nematode suspension in distilled water [2000 infective juveniles (IJs)/ml]. As control treatment, only the suspension of the nematode was used. After 48 hours, the viability and the infectivity of the nematode on the larvae of Tenebrio molitor were assayed. The effect of products on the symbiont bacterium was also evaluated. Suspension with 108 CFU (colony forming units)/mL were inoculated in culture medium and three paper discs added (control treatment – distilled water, comparison standard – neomycin, and a disc treated with each product) and the growth was evaluated after 24 hours. All the products reduced the viability of S. arenarium, although only the chlorine-based disinfectant caused reduction above 55%. For the infectivity, the chlorine-based product and the insecticide cipermil reduced in 100% this activity and were considered harmful based on E%. All the products affected the bacterial growing.